Experimental Study on Static Load of Large-Diameter Piles in Nonuniform Gravel Soil. (11th July 2020) - Zhao, Baoyun; Wang, Xiaoping; Yang, Mijia; Liu, Dongyan; Liu, DongSheng; Sun, Shuguo
Abstract : With the development of tourism, the number of multistorey buildings in mountain areas is increasing gradually, and the requirements of the form and bearing capacity of foundation in landslide areas are getting more demanding than ever. In-situ testing of rock and soil mass in slope area has important practical significance for improving the stability of building foundation. Taking a project in Baishi Mountain located in southwest of China as an example, firstly, the geological structure and mechanical properties of soil are analyzed. Then, two types of pile foundations, i.e., empty-bottom pile foundations and solid-bottom pile foundations, are designed based on the characteristics of the geological structure for carrying out the static load test on pile foundation. The test results are as follows: (a) the load settlement curve (Q-S) of the empty-bottom test pile shows a steep drop, while the Q-S curve of the solid-bottom test pile shows a gradual change, showing that the end-bearing friction pile's property and the ultimate bearing capacity of the solid-bottom pile are higher than those of the empty-bottom pile. (b) The maximum lateral friction of the four test piles is 139.158 kPa, 148.015 kPa, 150.828 kPa, and 154.956 kPa, respectively. (c) The shaft skin resistance under ultimate load is coming close to the maximum value, and the maximum values are 9.792 mm, 7.939 mm, 9.881 mm, and 14.97 mm, respectively. Research results can serve as design bases for the pile foundation of multistorey buildings located in landslide areas of Baishi Mountain in the southwest of China and also as references for the engineering application of pile foundation in similar geological fracture areas.